1995
DOI: 10.1002/art.1780380608
|View full text |Cite
|
Sign up to set email alerts
|

Serum hyaluronic acid level as a predictor of disease progression in osteoarthritis of the knee

Abstract: Objective. To investigate the prognostic value of serum hyaluronic acid (HA) and keratan sulfate (KS) levels in relation to tibiofemoral osteoarthritis (OA) of the knee.Methods. Clinical and demographic data were collected on 94 patients. Radiographs were obtained at study entry and at 5-year followup. Disease progression was defined as 2 mm of joint space narrowing of any tibiofemoral compartment, and/or knee joint surgery during the study period. Serum HA and KS were measured and levels were correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
1
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(119 citation statements)
references
References 23 publications
6
105
1
2
Order By: Relevance
“…Progression was defined as radiologic progression in almost all studies. Only 4 studies (11,19,23,24,45) (15%) also reported on a clinical outcome (total knee replacement).…”
Section: Resultsmentioning
confidence: 99%
“…Progression was defined as radiologic progression in almost all studies. Only 4 studies (11,19,23,24,45) (15%) also reported on a clinical outcome (total knee replacement).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the key enzyme in cartilage destruction has not been clearly elucidated, and families of enzymes, including matrix metalloproteinases (MMPs) (1,2), serine proteases (3), and a novel "aggrecanase" (4), have been suggested to contribute to cartilage destruction. In the studies that have focused on human articular cartilage, it has been observed that MMP-3 may be by far the major MMP in cartilage destruction.…”
Section: To the Editormentioning
confidence: 99%
“…To the Editor: Sharif and colleagues have reported findings, from a study of 94 patients with knee osteoarthritis (OA), suggesting that serum hyaluronate levels could predict outcome in OA of the knee and that a single measurement of the keratan sulfate (KS) epitope 5-D-4 might not be useful as a prognostic marker of OA (1). Moreover, the prognostic value of serum cartilage oligomeric matrix protein (COMP) has been investigated in a set of 57 patients with knee OA ( 2 ) .…”
Section: Serum Biologic Markers As Predictors Of Disease Progression mentioning
confidence: 99%
See 1 more Smart Citation
“…These 2 markers have been used in human studies and are shown to be indicative of various aspects of OA. HA is a glycosaminoglycan found in synovium and cartilage that predicts disease outcome in knee (39) and hip OA (40) and correlates with OA progression (39)(40)(41)(42)(43)(44)(45). To date, there are few data regarding serum or synovial fluid biomarker levels following articular fracture and the subsequent development of arthritis.…”
mentioning
confidence: 99%